Analisis Kemampuan Kerjasama Anak Usia Dini Kelompok B1 TK Pembina Agropilitan - Fiola Indah Putri Pratama; Marsya Cikita; Tira Talangani; Wayan Indriani; Herlisna Kuku (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to analyze cooperative abilities in early childhood (AUD) and the factors that influence them. The subjects of this research were children aged 4 to 5 years who were in Agropolitan Kindergarten in the Toto area, South, Kabila District, Bone Bolango Regency. This research uses a qualitative approach with descriptive methods, which involves direct observation of children's social interactions in group activities, interviews with educators, and analysis of documents related to children's social development. The data analysis technique used is quantitative analysis. The results of the research show that the ability to collaborate in early childhood develops gradually, from the ability to follow group instructions at the age of 4-5 years, to the skills to resolve conflicts and work in group projects at the age of 5-6 years. Factors that influence children's cooperative abilities include support from the family environment, educational approaches based on collaborative learning, and peer influence. However, several challenges were found, such as children's difficulty in sharing, lack of social experience, and differences in individual character. As a solution, it is recommended that educators and parents be more active in developing children's social skills through collaborative games, project-based learning, as well as empathy training and constructive conflict resolution. It is hoped that this research will provide insight into the development of teaching methods that can support the development of cooperation in early childhood.